Hematological Changes in Whole Blood Stored in Blood Bags Containing CPDA-1 Over a Period of 28 Days - Chaurasiya, Anand Kumar; Patel, Amit Kumar; Prasad, Shyam Babu; Bhaskar, Ravi Kumar; Jha, Udaykant (Med Phoenix, 2023)
Introduction: Blood storage is needed to ensure a readily available and safe blood supply. During blood storage in blood bank, biochemical and physical properties of RBCs are altered because of storage conditions. In normal conditions in the body circulation, these do not occur as optimum pH, temperature, nutrient concentration and waste products removal are maintained. The aim of this study was to observe the changes in whole blood stored in blood bags containing CPDA-1 over a period of 28 days. Materials and Methods: This was a hospital based observational study conducted in Blood Bank, National Medical College and Teaching Hospital (NMCTH), Birgunj. A total of 450 ml blood was drawn from 50 healthy volunteer donors into blood bags containing CPDA–1 anticoagulant and placed on the quarantine shelf of the blood bank refrigerator maintained at 2-8o centigrade. The blood bags were screened for HCV, HBsAg, syphillis and HIV. Ten milliliters blood was withdrawn from the blood bags on 1st, 7th, 14th, 21st, and 28th day and tested for hematological parameters using Yumizen H550 (HORIBA) fully automated hematology analyzer. Results: At the end of 28 days, whole blood storage in CPDA-1 revealed significant decrease in WBC (T = 4.79, p < 0.01) and platelets count (T=180.09, p < 0.01). Hematocrit increased significantly after 21 days of storage (T = 40.86, p < 0.01). MCHC and MCH also demonstrated significant increase during the storage period (T = 37.32, p < 0.01) and (T = 29.38, p < 0.01), respectively. Conclusion: WBC and platelets are significantly altered (decreased) when stored in blood bags containing CPDA- 1 after one week period. The study recommends whole blood transfusion before seventh day of donation in order to avoid the adverse outcome of hematological changes in stored blood. In case it has to be used beyond one week, then it should be leukodepleted before storage.